Friction-stir incremental sheet forming of aluminum alloy and metal matrix composite - Azpen, Qasim Mahalhal (2018)
Currently, there is a growing market for manufacturing customized, rapid prototyping and low-cost sheet parts with small to medium batches (particularly in transportation, artificial medical alternatives, and aerospace industries). Incremental Sheet Forming (ISF) was born as an advanced sheet forming process to perfectly fit previous requirements. ISF is described to have inherent flexibility, high formability, and low-cost and forming forces compared to traditional sheet metal forming processes. Nevertheless, increasing demands to utilize the lightweight materials in various applications has placed this developed process in a critical challenge to deal with low formability materials at room temperature. Among all heat-assisted ISF processes, frictional stir-assisted Single Point Incremental Forming (SPIF) was presented in this study. Besides the mentioned advantages of ISF, frictional stir-assisted SPIF displays superior benefits as it does not require an external heating source and has a better final surface finish than the other types. Accordingly, this technique was used to improve the formability of two lightweight materials: aluminum alloy AA60601-T6 and metal matrix composite AA6061/20%SiCp-T1 sheets. The study focuses on the investigation of the process aspects, which include process formability indicators, forming forces, and surface roughness. Tool rotation speed, feed rate, step size, and tool diameter are proposed as process parameters to evaluate their impact on the output responses. In this regard, Taguchi Design of Experiment (DoE) technique and the analysis of variance (ANOVA) were employed to design the experimental work and statistically evaluate the impact of each parameter. For AA6061-T6 experiments, the rotation spindle speed was the most dominant parameter that affects formability and forming forces where the percentage contributions of this parameter are 90% and 73%, respectively. On the other hand, the tool diameter has a significant impact on the internal surface roughness with a percentage contribution of 93%. The values of the determination coefficients R2 are 95, and 98% for the formability and surface roughness, respectively. From the results comparison of the two materials, maximum angles, maximum height, minimum forming force, minimum surface roughness are 66.15ᵒand 48ᵒ; 27.46 mm and 11.55 mm; 2.4478 KN and 2.1273 KN; 0.3 μm and 1.741 μm, for AA606-T6 and AA6061/20%SiCp-T1, respectively.